Uswatun Hasanah Guru Perspektif Syekh Al-Zarnuji dalam Kitab Ta’lim Al Muta’allim - Yulia Hadi; Moch Mahsun; Ihya’ Ulumudin (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2021)
The research is focuses on how the habituation of behavior through good examplary of teacher in the view of Syekh Imam al-Zarnuji, and how are the espousals and obstacles to make the habituation of the students’ behavior through ‘uswatun hasanah’ from the teacher at SMP Al-Ikhlash Lumajang. The research method is qualitative using Grounded Theory, the data collection is using observation, interview and documentation, and the analysis data is using inductive, deductive and descriptive. Based on the data analysis shown that the students’ behavior in perspective of Syekh Al-Zarnuji, it has been mostly impelemented at SMP Al-Ikhlash Lumajang. Firstly, the students’ behavior toward their teachers; they are honor deeply relating to the whole teachers’ thing. Secondly, they are honeor deeply of the knowledges such as make the books are neat in the bookshelves. Thirdly, the competencies of teacher were needed as the figure of uswatun hasanah perspective of Syekh al-Zarnuji has been the characteristics of each teacher at SMP al-Ikhlash Lumajang. The espousal factors of such habitual behavior are the recruitment of quality teachers from Lemdik al-Ikhlash, upgrading teachers, the bahavior has been the characteristic of teachers, adequate facilities, and continuity. While, the obstacles factors such as the input of students were from the various educational background in the beginning of school year.